2020
DOI: 10.1002/cbin.11330
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐interleukin‐5‐neutralizing antibody attenuates caradiac injury and cadiac dysfunction by aggravating the inflammatory response in doxorubicin‐treated mice

Abstract: Previous studies have demonstrated that interleukins (ILs) are closely associated with doxorubicin (DOX)-induced cardiac injury. IL-5 is an important member of the IL family, and this study was performed to investigate whether IL-5 affects DOX-induced cardiac injury and its underlying mechanisms. The cardiac IL-5 expression was first detected and the results showed that cardiac IL-5 levels were significantly lower in DOX-treated mice, and IL-5 was mainly derived from cardiac macrophage (Mø). In addition, some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…To examine the expression of IL‐5 in sepsis, IL‐5 expression in mice treated with LPS or received cecal ligation surgery was measured, and the results showed that both treatment with LPS and cecal ligation decreased IL‐5 expression, which suggests that IL‐5 participates in the progression of sepsis. In addition, previous studies reported that inflammation‐mediated substances, such as doxorubicin, Ang II, and a high‐fat diet, decreased IL‐5 expression in mice 13–16 . Our data showed that both LPS and cecal ligation decreased IL‐5 expression in mice.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…To examine the expression of IL‐5 in sepsis, IL‐5 expression in mice treated with LPS or received cecal ligation surgery was measured, and the results showed that both treatment with LPS and cecal ligation decreased IL‐5 expression, which suggests that IL‐5 participates in the progression of sepsis. In addition, previous studies reported that inflammation‐mediated substances, such as doxorubicin, Ang II, and a high‐fat diet, decreased IL‐5 expression in mice 13–16 . Our data showed that both LPS and cecal ligation decreased IL‐5 expression in mice.…”
Section: Discussionsupporting
confidence: 73%
“…4,16,28,33 M1 macrophages can release a variety of important pro-inflammatory factors, which are closely related to myocardial cell apoptosis, a similar effect was also observed in sepsis. 4,5,16,28 After confirming that IL-5 deficiency promotes LPS-induced M1 macrophage differentiation in vitro, we determined whether myocardial cell apoptosis was mediated by the differentiation of M1 macrophages by coculturing myocardial cells with macrophages. The results showed that coculture with IL-5−/− macrophages significantly increased myocardial cell apoptosis after LPS administration and was significantly decreased by JSH-23 treatment.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The interleukin (IL) family is a multifunctional cytokine family, several members of which have been reported to regulate DOX-induced acute cardiac injury in mice. In a recent study, neutralization of IL-5 was reported to promote the secretion of various cardiac cytokines and to reduce cardiac function in DOX-treated mice [ 5 ]. In a mouse model, overexpression of IL-10 by adeno-associated virus 1 (AAV-1) significantly reversed DOX-induced cardiotoxicity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%